Human dermal fibroblast adhesion on Ti-7.5Mo after TiO2 nanotubes growth - do Amaral Escada, Ana Lucia [UNESP] (2017)
Vertically aligned TiO2 nanotubes have been grown on Ti-7.5Mo by anodization and the growth of human dermal fibroblast on such nanotubes were investigated. The TiO2 nanotubes were characterized by means of field emission scanning electron microscopy (FEG-SEM) and X-ray diffraction (XRD). To characterize the cell morphology and viability it was used a scanning electron microscope and MTT assay after 1, 4 and 7 days cell. The results showed that cell proliferation was evident over the duration of experiment, but it was higher at day 4 on polished Ti-7.5Mo.